Laparoskopinis žarnos vientisumo atkūrimas po Hartmanno operacijos - Stašinskas, Algimantas; Stanaitis, Juozas (Lietuvos chirurgija, 2012)
Center of General Surgery, Faculty of Medicine, Republican Vilnius University Hospital, Šiltnamių Str. 29, Vilnius, Lithuania E-mail: astasinskas@yahoo.fr; Juozas.Stanaitis@mf.vu.lt, juozas.stanaitis@vgpul.lt Introduction A change in procedure from open to laparoscopic reversal of Hartmann’s colostomy was implemented at our department between May 2009 and December 2010. The aim of the study was to investigate whether this change was beneficial for the patients. Methods The medical records of all patients who underwent colostomy reversal after a primary Hartmann’s procedure during the period from May 2009 to December 2010 were reviewed retrospectively in a case control study. Results A total of 13 patients were included. Six had a laparoscopic and 7 an open procedure. The two groups matched with regard to age, sex, the American Society of Anaesthestist (ASA) score, body mass index and indication for Hartmann’s operation. A significantly longer operation time was found for laparoscopic than for open surgery (median 285 versus 158 minutes, p < 0.001), but with a less blood loss (median 100 versus 600 ml, p < 0.001), faster return of bowel function (median three versus four days, p < 0.01) and a shorter postoperative hospitalization (median four versus six days, p < 0.01). No intraoperative complications occurred. One laparoscopic operation was converted (16.6%). There was no difference in postoperative complications between the two groups (10 versus 14%) and no anastomotic leaks. The total mortality was 0. Conclusion It is possible for trained laparoscopic general surgeons to perform laparoscopic reversal of Hartmann’s procedure as safely as in open surgery and with a faster recovery, shorter hospital stay and less blood loss despite a longer knife time. Therefore, it seems reasonable to offer patients a laparoscopic procedure at departments skilled in laparoscopic surgery and use it for standard colorectal surgery. Key words: laparoscopic reversal of Hartmann’s colostomy; restoration of intestinal continuity